Multiplication of radicals using the distributive property

Learn how to perform multiplication of radicals with some carefully chosen examples using the distributive property. Study the example below carefully. If you did not understand it or need more examples to master the topic, keep reading.

Multiplication of radicals

More examples showing how to do multiplication of radicals

Example #1

$$ (\sqrt{3} + \sqrt{2}) × (\sqrt{3} - \sqrt{2}) $$

Here is how you can use the distributive property to do this multiplication.

$$ (\sqrt{3} + \sqrt{2}) × (\sqrt{3} - \sqrt{2}) $$
$$ = \sqrt{3}×\sqrt{3} - \sqrt{3}×\sqrt{2} + \sqrt{2}×\sqrt{3} - \sqrt{2}×\sqrt{2} $$
$$ = \sqrt{3}×\sqrt{3} - \sqrt{3}×\sqrt{2} + \sqrt{2}×\sqrt{3} $$
$$ - \sqrt{2}×\sqrt{2} $$
$$ = \sqrt{3 × 3} - \sqrt{3 × 2} + \sqrt{2 × 3} - \sqrt{2 × 2} $$
$$ = \sqrt{9} - \sqrt{6} + \sqrt{6} - \sqrt{4} $$
$$ = \sqrt{9} - \sqrt{4} $$

= 3 - 2 

=  1

Did you notice that the multiplication has the format (a + b) x (a - b)?

 (a + b) x (a - b) = a2 - b2

Therefore, next time, there is absolutely no need to do at all this math above.

$$ (\sqrt{3} + \sqrt{2}) × (\sqrt{3} - \sqrt{2}) = (\sqrt{3})^2 - (\sqrt{2})^2 $$
$$ Notice \ that (\sqrt{3})^2 = 3 $$
$$ Notice \ also \ that (\sqrt{2})^2 = 2 $$
$$ In \ general,\sqrt{a} ×\sqrt{a} = (\sqrt{a})^2 = a $$


Example #2

$$ (\sqrt{7} + \sqrt{5}) × (\sqrt{7} - \sqrt{5}) $$

Once again, notice that the multiplication has the format (a + b) x (a - b).

Therefore, you can just use the formula below to quickly get an answer:

(a + b) x (a - b) = a2 - b2

$$ (\sqrt{7} + \sqrt{5}) × (\sqrt{7} - \sqrt{5}) $$
$$ = (\sqrt{7})^2 - (\sqrt{5})^2 = 7 - 5 = 2 $$


Example #3

$$ (\sqrt{6} + \sqrt{9}) × (\sqrt{6} - \sqrt{9}) = 6 - 9 = -3 $$


Example #4

$$ (\sqrt{4} - 2\sqrt{12}) × (\sqrt{4} + \sqrt{12}) $$
$$ = \sqrt{4} × \sqrt{4} + \sqrt{4} × \sqrt{12} -2\sqrt{12} ×\sqrt{4} -2 \sqrt{12} × \sqrt{12} $$
$$ = (\sqrt{4} × \sqrt{4} + \sqrt{4} × \sqrt{12} -2\sqrt{12} ×\sqrt{4} $$
$$ -2 \sqrt{12} × \sqrt{12} $$
$$ = 4 + 2 × \sqrt{12} -2\sqrt{12} ×2 -2 × 12 $$
$$ = 4 + 2\sqrt{12} -4\sqrt{12} -24 $$
$$ = -2\sqrt{12} - 20 $$

Recent Articles

  1. Time-series Data - Definition and Example

    May 07, 21 02:29 PM

    A time-series data shows information about the same subject or element of a sample or population for different periods of time.

    Read More